Digital transformation in Africa: results from a strategic foresight exercise in Cameroon - (:unkn) unknown (My University, 2023)
Digital transformation is a key issue today in Africa. Some organizations alreadychanged their practices and they are early adopters (Rogers, 1962, Mercuri Chapuisand de Bovis, 2023) but the diffusion of innovation is a long cycle to follow. Thisresearch, through a qualitative methodology, contributes to the theory of the diffusionof innovations by emphasizing the role of strategic foresight in the success of digitaltransformations in general and, to the literature on the impact of digitaltransformations on the competitiveness of African organizations in particular. Finally,it can be useful to African leaders and entrepreneurs who wish to succeed in theprocess of digital transformation of their organizations, in order to improve theircompetitiveness.
Keywords: African Research